Comparison Of Feasibility Of Concrete And Asphalt Road With Analityc Hierarchy Process (AHP) Method - Apriyanto, Agus (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2022)
This study specifically tries to apply the AHP (analytic hierarchy process) method in the interest of formulation and decision making in the field of engineering, especially for evaluating the comparison of road construction feasibility between asphalt and concrete roads. It is hoped that through this study it can be proven that the AHP method, which is widely used in management decision making, is reliable enough to be applied in engineering and engineering, so that it can assist policy makers in the process of making objective decisions, especially in government circles. This study method includes data collection and analysis methods. For data collection, this study uses a questionnaire method that contains questions related to technical and non-technical factors that are used to assess the feasibility of a road. A total of 16 questions in the questionnaire. Questionnaires were distributed randomly to around 30 respondents who were divided into various groups such as the Department of Highways, consultants, university lecturers, contractors and the general public around the Demak – Godong highway. The results of the questionnaire in the form of answers from respondents were then recapitulated and searched for the dominant answer for each question. The dominant answer is then scored based on the Saaty rating scale. These values ​​are then formed matrices with certain patterns. The AHP method was then applied to analyze these matrices. The results of calculations using the AHP method are in the form of eigenvectors where each value in the vector indicates the value of the proposed alternative (in this case asphalt and concrete construction). From the results found in the analysis, recommendations can then be given as follows: 1) Changes in construction from asphalt to concrete as is currently being carried out on the Demak – Godong highway need to be supported considering that in many ways concrete construction is more feasible than asphalt construction. from this study and 2) the data for the AHP method in this study rely on respondents' assessments of the proposed factors, because the assessments will vary greatly from one another (as indicated in the frequency distribution of the data), the increase in the number of respondents with wider sources involving experts needs to be done in order to maintain data consistency.